PD-L1 Regulates Platelet Activation and Thrombosis via Caspase-3/GSDME Pathway - Li, Yulong; Xin, Guang; Li, Shiyi; Dong, Yuman; Zhu, Yuda; Yu, Xiuxian; Wan, Chengyu; Li, Fan; Wei, Zeliang; Wang, Yilan; Zhang, Kun; Chen, Qingqiu; et al. (Frontiers in Pharmacology, 2022)
Platelets play a central role in hemostasis and thrombosis, regulating the occurrence and development of thrombotic diseases, including ischemic stroke. Programmed death ligand 1 (PD-L1) has recently been detected in platelet, while the function of PD-L1 in platelets remain elusive. Our data reveal a novel mechanism for the role of PD-L1 on platelet activation and arterial thrombosis. PD-L1 knockout does not affect platelet morphology, count, and mean volume under homeostasis and without risk of bleeding, which inhibits platelet activation by suppressing outside-in-activation of integrin by downregulating the Caspase-3/GSDME pathway. Platelet adoptive transfer experiments demonstrate that PD-L1 knockout inhibits thrombosis. And the absence of PD-L1 improves ischemic stroke severity and increases mice survival. Immunohistochemical staining of the internal structure of the thrombus proves that PD-L1 enhances the seriousness of the thrombus by inhibiting platelet activation. This work reveals a regulatory role of PD-L1 on platelet activation and thrombosis while providing novel platelet intervention strategies to prevent thrombosis.